CRITICAL THINKING AND ITS TEACHING TO STUDENT YOUTH IN THE PERIOD OF GLOBALIZATION - Davletmuratov K. X. (European Science Publishing, 2025)
The article reveals questions about teaching students to think critically. independent-minded students and future highly qualified personnel with modern knowledge and high spiritual and moral qualities, modernization of higher education.
Keywords: Critical thinking, parliamentary debates, higher education, Uzbekistan, modern educational technologies, pedagogical methods, student development, educational modernization, history of parliamentarism, cognitive processes.